ENERGY POLICY AND ENERGY PROJECTS IN CENTRAL EURASIA - TOMBERG, Igor (CENTRAL ASIA AND THE CAUCASUS, 2007)
In Central Asia, energy policy and energy projects as part of the fuel and energy complex and regional economy as a whole are two sides of the same coin. In other words, the key energy projects that determine the development trends and major parameters of the republics’ fuel and energy complexes for many years to come are, as a rule, closely connected with the main strategic foreign policy trends of those who rule Kazakhstan, Turkmenistan, and Uzbekistan. The main strategic actors (Russia, the United States, EU, and China) are exerting their influence on the local developments in the energy sphere. The second echelon (Iran, Turkey, Azerbaijan, Georgia, Ukraine, and Poland) recently joined the struggle over influence in the energy sphere. The list of those involved is even longer: Japan, India, Malaysia, and South Korea are ready with their money to pursue their commercial and resource-related interests. The long list of those wishing to have a fin-ger in the Central Asian resource pie explains the local countries’ multi-vector energy policy. While bringing certain short-term political and even eco-nomic dividends, this policy interferes with long-term strategic decisions and slows down progress in the region’s fuel and energy complex. Here are several recent examples: the al-ready commissioned or planned pipelines depend for their continued functioning or even realization on Central Asian involvement. The Baku-Tbilisi-Ceyhan (BTC) pipeline will not reach its designated annual capacity of 50 million tons of oil without Kazakhstan’s oil. The planned Trans-Cas-pian pipeline (along the seabed) will never be realized if the Central Asian countries refuse to use it. This explains the heightened attention (bordering on pressure) to the leaders of Kazakhstan and Turkmenistan. The aim is obvious: the two countries should be removed from Russia’s gas-and oil transport orbit to channel their fuel to Europe bypassing the Russian Federation and its pipeline system.